Family Stigma Correlation with Shackling in Schizophrenia Patients in Psychiatric Hospital of Bali Province - Desak Made Ari Dwijayanti; Putu Herry Dharmawan (Alma Ata University Press, 2018)
Shackling in Indonesia becomes mental health problem showing that mental disorder patients have not gotten good or full treatment and proper human right yet. Stigma and discrimination for schizophrenia patients often get some treatment in which breaks human right it is caused by that mental disorder patients of do violance and aggresive action. The reason why the family perform Shackling.This study aimed to know the correlation between family stigma and shackling patients with schizophrenia. This study used correlational descriptive design with cross-sectional approach. It was conducted towards 45 respondents selected by sampling concecutive technique. The data was collected by using familys stigma and KKPD questionnaire.The result showed that the familys stigma for schizophrenia patients are mostly in often category as many as 24 respondents (53.3%). The willing of the family for shackling schizophrenia patients is mostly in high category as many as 20 respondents (44.4%). The result of Rank Spearman test showed p-value=0.000<0.05. It could be concluded that Ha was accepted which mean that there was a relationship between familys stigma and shackling for schizophrenia patients. RSJ Bali Province was suggested to give guidance and doing home visit for family that had high desires in shackling in order to prevent it after patient had been discharged from the psyciatric hospital. Keywords: family stigma, Shackling, schizophrenia